PENGUJIAN VARIABEL KETENAGAKERJAAN TERHADAP BIAYA STICKINESS - Windyastuti Windyastuti (Jurnal Keuangan dan Perbankan, 2013)
This study analyzed the effect of labor variable on the cost stickiness in Indonesian manufacturing industry. Theresearch data included sales, general and administration (SGA) and net sales of manufacturing companies thatgo public on the Indonesian stock effect. The data were supplemented by data of unions and regulations onseverance. This study used regression analysis based on panel data models. The results showed that sales, generaland administration (SGA) cost was sticky. The decreasing of the sales, general and administration (SGA) costwhen net sales decrease was smaller than the increase of this cost when equivalent increased in net sales. The laborunion increased the stickiness cost of SGA. The SGA cost did not decrease even though at the same time the netsales decreased. Furthermore, the larger severance pay did not increase stickiness SGA cost. When the net salesdecreased, the employer increased the sales cost in order to increase marketing activity so the net sales increasedagain. The increasing of sales cost in turn increased the cost of SGA.